Chemical Composition, Antifungal and Antioxidant Activity of Some Spice Essential Oils: Life Sciences-Microbiology for health care - Ghadah Saber Ibrahim; Manal Jameel Kiki (International Journal of Life Science and Pharma Research, 2022)
This study was carried out to determine the chemical composition of some spice essential oils, to test the radical scavenging and the anti-fungal activities of Cinnamon, Anise, Cumin and Caraway EOs. The essential oil compositions were determined by GC-MS and showed variation in its constituent for each type of oil. Major identified components were Cinnamaldehyde 81.79 % for Cinnamon EO (Ci-EO), Anethole 90.9% for Anise EO ( An-EO), (gamma-Terpinene 23.84%, beta.- Pinene 21.84%, Benzaldehyde, 4-(1-methylethyl) 20.00%, Carenal 17.50% and Benzene, 1-methyl-3-(1-methylethyl) 14.10%) for Cumin EO ( Cu-EO ) and (Carvone 52.27% and D-Limonene 47.13 %) for Caraway EO (Ca-EO). Antioxidant effectiveness was examined by the 2,2’-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method using different concentrations of EOs (2.5, 5.0, 10.0 , 20.0 , 40.0 , mg/ml) at different times. All essential oils have shown antioxidant activity. Based on their antioxidant capacity, four spice essential oils sorted in descending order: Cumin 87.4% > Anise 72.4% > Caraway 59.5 > Cinnamon18.2 % at high concentration 40.0, mg/ml at 120 min. These essential oils were also found to possess remarkable antifungal activity against tested pathogens like yeasts (Candida krusei ATCC 6258, Candida parapsilosis ATCC 22019) and fungi (Aspergillus niger, Aspergillus flavus and Aspergillus fumigatus) by using disc diffusion technique. Cu- EO showed 100% inhibition against A. niger, C. krusei and C. parapsilosis. For other tested fungi, the essential oils showed good to moderate inhibitory effects. Positive and important associations between mycelial growth inhibition of both pathogens and the antioxidant activity of the checked oils. These results showed tested essential oils could be used as a source of antioxidant and antifungal compounds which may find applications in pharmaceutical and food industries.